Internet of Things on Electrical Energy Monitoring Using Multi-Electrical Parameter Sensors - Risfendra Risfendra; Gheri Febri Ananda; Alphin Stephanus (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2021)
This study aims to apply the Internet of Things to monitoring electricity energy consumption. The system is designed to replace the manual and conventional measurement of electrical energy. Uncontrolled use of electricity is one of the causes of high levels of electrical energy consumption. Therefore, consumers need to know the amount of electrical energy consumption in real-time. The device is designed using the PZEM-004T which is used as a sensor to read electrical multi-parameter, Arduino as the main control, and ESP8266 as a data sender on the Cloud system. The test results showed that the device has been able to read and display electricity quantity data in the form of voltage, current, power, and electricity tariff accumulation in real-time displayed on the ThingSpeak platform. The test on the PZEM-004T sensor has an accuracy rate of 94.96% for reading current values and 99.42% for reading voltage values. Penelitian ini bertujuan untuk menerapkan teknologi Internet of Things pada monitoring konsumsi energi listrik. Sistem dirancang untuk menggantikan pengukuran energi listrik yang masih manual dan konvensional. Penggunaan listrik yang tidak terkontrol merupakan salah satu penyebab tingginya tingkat pemakaian energi listrik. Oleh karena itu, konsumen perlu mengetahui jumlah pemakaian energi listrik secara realtime. Alat dirancang menggunakan PZEM-004T yang digunakan sebagai sensor untuk membaca multi-parameter listrik, Arduino sebagai kendali utama, dan ESP8266 sebagai pengirim data pada sistem Cloud. Hasil pengujian menunjukan bahwa alat telah mampu membaca dan menampilkan data besaran listrik berupa tegangan, arus, daya, dan akumulasi tarif listrik secara realtime yang ditampilkan pada platform ThingSpeak. Pengujian pada sensor PZEM-004T memiliki tingkat akurasi 94.96% untuk pembacaan nilai arus dan 99. 42% untuk pembacaan nilai tegangan.